Perception of the Zika virus infection and its influence on Zika prevention practices by pregnant women at the Region 5 Health Promotion Center in Thailand (Medical Journal of Indonesia, 2018)
Background: The Zika virus (ZIKA) infection in pregnant women causes microcephaly, a brain disorder resulting in severe birth defects. The objective of this study was to identify the factors that influence Zika prevention practices by pregnant women at the Region 5 Health Promotion Center in Thailand.Methods: A cross-sectional study applied a survey method to collect data from pregnant women between 18 and 45 years of age. The sampling method used multistage random sampling. The data were analyzed using descriptive statistics and multiple linear regression analysis.Results: The findings indicated that 5 of 12 factors could significantly predict Zika prevention practices of pregnant women at the Health Promotion Center Region 5 in Thailand: education, smoking behavior, check-up status during pregnancy, perception of susceptibility, and perception of benefit.Conclusion: The results show a direct correlation between the perception of susceptibility and benefit and Zika prevention practices. Policies for promoting Zika knowledge and preventive behavior by providing information about Zika should focus on changing the thoughts, attitudes, and beliefs of pregnant women and their families.